Do golpe de 2016 ao bolsonarismo: o neofascismo no Brasil - Almeida, Alex Fernandes Silva de (2021)
The present work aims to characterize fascist and Nazi movements and to show the emergence of neo-fascism in Brazil. We also seek to conceptualize the terms left, center and right in the context in which they are used to determine political movements and positions. These nomenclatures, because they are widely used in the current political and journalistic scenario, are almost always reproduced in the wrong way. Tutorial A, then, is to clarify the main ideas around these terminologies. In addition, we will discuss the influence of the media in the political events surrounding the events between 2014 and 2020. To this end, a survey sought to analyze the actions and media discourses around the impeachment of Dilma Rousseff, the inauguration and the government of the vice Michel Temer and the election of Bolsonaro. It was also sought to highlight the discursive practices and scholarship actions that can fit the neo-fascist pattern. The study is a bibliographic and documentary research. The theoretical framework is based on: NEVES FILHO (2020), GOMIS (1997), LENHARO (2006), LÖWY (2019), SOUZA (2017), STEVEN and ZIBLAT (2018), TRENTO (1993), TROTSKI (2019), among others